Advertisement embedding for online videos - Yong, Xin Yu (2014)
Advertising methods have been undergoing changes as the audiences’ viewing habits have already undergone changes in the recent years. Advertisements are now hidden in almost every gap that you would normally have neglected. As such, the number of advertisements that you can see nowadays can reach an uncountable figure. With so many advertisements hidden everywhere, it would definitely get on your nerves in one way or another. To avoid such situations, this project was developed in aim of creating a higher relevance between the advertisements and the user.